2004
DOI: 10.1161/01.hyp.0000138688.78906.6b
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Vascular Endothelial Growth Factor in Angiotensin II–Induced Vascular Inflammation and Remodeling

Abstract: Abstract-Angiotensin II (Ang II) upregulates vascular endothelial growth factor (VEGF) and activates vascular inflammation. However, the decisive role of VEGF in Ang II-induced vascular inflammation and remodeling has not been addressed. Ang II infusion to wild-type mice increased local expression of VEGF and its receptors in cells of aortic wall and plasma VEGF, and caused aortic inflammation (monocyte infiltration) and remodeling (wall thickening and fibrosis).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(123 citation statements)
references
References 50 publications
8
110
0
5
Order By: Relevance
“…Angiotensin II up-regulates VEGF mRNA expression in vascular and renal cells (VSMCs, endothelial cells, cardiac myofibroblasts, mesangial cells), primarily through the AT1 receptor. This involvement of Ang II in the early phase of vascular inflammation is mediated independently of hemodynamic changes [47].…”
Section: Part II -Role Of the Renin-angiotensin-aldosterone System Onmentioning
confidence: 99%
“…Angiotensin II up-regulates VEGF mRNA expression in vascular and renal cells (VSMCs, endothelial cells, cardiac myofibroblasts, mesangial cells), primarily through the AT1 receptor. This involvement of Ang II in the early phase of vascular inflammation is mediated independently of hemodynamic changes [47].…”
Section: Part II -Role Of the Renin-angiotensin-aldosterone System Onmentioning
confidence: 99%
“…Furthermore, we did not find any difference in the inflammatory biomarkers in type 1 diabetic patients who were treated with blood pressure-lowering drugs compared with the normotensive patients. It is known that angiotensin II may stimulate IL-6 and other inflammatory biomarkers (20,21). Thus, it is possible that administration of angiotensin II blockers, as given to six patients, would reduce the levels of inflammatory biomarkers.…”
Section: Correlation Between Inflammatory Indicators and Metabolic Mementioning
confidence: 99%
“…1-4 RAS activation and increased levels of AngII can be seen in patients with cardiovascular diseases, including atherosclerosis, hypertension, cardiac hypertrophy and heart failure. 1, 5,6 Conversely, inhibition of RAS activation by angiotensin receptor blockade has been shown to significantly improve patient survival and limit the progression of cardiac remodeling and heart failure. 7 Investigations in small animals have confirmed that AngII exposure can result in myocardial fibrosis.…”
Section: Introductionmentioning
confidence: 99%